2019
DOI: 10.3390/ijms21010063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regorafenib, a Multi-Kinase Inhibitor, on Conjunctival Scarring in a Canine Filtration Surgery Model in Comparison with Mitomycin-C

Abstract: Regorafenib eye drops were developed for treating age-related macular degeneration. This study aimed to investigate the effects of this multi-kinase inhibitor on intraocular pressure (IOP), bleb formation, and conjunctival changes in a canine filtration surgery model. Glaucoma filtration surgery models were created in 24 eyes of 24 beagles. In experiment 1 (Ex 1), regorafenib eye drops (regorafenib group: n = 6) or a vehicle (control group, n = 6) were instilled twice daily for 4 weeks postoperatively. In expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Previous clinical trials have demonstrated the efficacy of one particular medication from the aforementioned list in treating open angle glaucoma or ocular hypertension ( Brigell et al, 2022 ). In animal studies, three medications have exhibited anti-fibrotic properties and neuroprotective effects ( Nemoto et al, 2019 ; Zhang et al, 2019 ; Kim et al, 2021 ). Additionally, two medications have been found to interfere with the TGF-β/p38 signaling pathway, modify cellular structure, and reduce extracellular matrix (ECM) at the cellular level ( Luo et al, 2014 ; Song et al, 2022 ) ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous clinical trials have demonstrated the efficacy of one particular medication from the aforementioned list in treating open angle glaucoma or ocular hypertension ( Brigell et al, 2022 ). In animal studies, three medications have exhibited anti-fibrotic properties and neuroprotective effects ( Nemoto et al, 2019 ; Zhang et al, 2019 ; Kim et al, 2021 ). Additionally, two medications have been found to interfere with the TGF-β/p38 signaling pathway, modify cellular structure, and reduce extracellular matrix (ECM) at the cellular level ( Luo et al, 2014 ; Song et al, 2022 ) ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To explain this phenomenon, unlike tube shunt surgery, which produces delayed drainage of AH to the equatorial region of the eye due to the distance between the location of filtration and the conjunctival incision, trabeculectomy causes an immediate filtration of AH near the conjunctival incision that increases the risk of leakage. In addition, the application of antimetabolites such as mitomycin C (MMC) and 5-fluorouracil (5-FU) in trabeculectomy is considered to be related since they are thought to be the cause of an increased probability of bleb leakage 78. Histological studies of MMC blebs have shown an irregular surface epithelium and a largely avascular and acellular subepithelium of loosely arranged connective tissue, which may explain the delayed bleb leaks seen frequently after MMC-augmented glaucoma surgery 79.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the application of antimetabolites such as mitomycin C (MMC) and 5-fluorouracil (5-FU) in trabeculectomy is considered to be related since they are thought to be the cause of an increased probability of bleb leakage. 78 Histological studies of MMC blebs have shown an irregular surface epithelium and a largely avascular and acellular subepithelium of loosely arranged connective tissue, which may explain the delayed bleb Open access leaks frequently after MMC-augmented glaucoma surgery. 79 The association between delayed bleb leaks and thin-walled, avascular blebs has been previously reported, with these leaks being more frequent after full-thickness procedures.…”
Section: Open Accessmentioning
confidence: 99%